E.P. Fedorov is the high classic astronomer (to the 95th birth anniversary) - Korsun', A.A. (Кинематика и физика небесных тел, 2005)
Evgen Pavlovych Fedorov (1909–1986) was a well known astronomer who played a very important role in the fundamental astrometry and geodynamics in the second half of the 20th century.